Joint Impact Assessment of CTA's support to FANRPAN (2003-2013) - Alfred, Sharon; Lock, Karen (Technical Centre for Agricultural and Rural Cooperation, 2020)
CTA’s support with partnerships since 2004 and valued at 932,958 Euros has enabled FANRPAN to raise its profile, increase awareness among a wider audience of its activities and projects, and improve the frequency and quality of its communication and advocacy products to policy-makers, Network members and FANR stakeholders. CTA’s support has largely been directed towards supporting FANRPAN’s communication and advocacy efforts, which are important aspects of the work of a policy research and knowledge network. CTA’s funding has indirectly supported and contributed towards organisational change and growth.